2011
DOI: 10.1002/ijc.26181
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab ± chemotherapy enhances dendritic cell‐mediated phagocytosis of colon cancer cells and ignites a highly efficient colon cancer antigen‐specific cytotoxic T‐cell response in vitro

Abstract: Cetuximab is a human/mouse chimeric IgG1 monoclonal antibody (mAb) to epidermal growth factor receptor, approved for colorectal carcinoma treatment in combination with chemotherapy. The immune-mediated effects elicited by its human fraction of crystallization moiety might critically contribute to the overall anti-tumor effectiveness of the antibody. We therefore investigated cetuximab ability to promote colon cancer cell opsonization and phagocytosis by human dendritic cells (DCs) that are subsequently engaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 45 publications
2
54
0
Order By: Relevance
“…Correale and colleagues found that a cytotoxic lymphocyte antitumor response was stimulated by dendritic cell (DC)-mediated cross-priming of antigens derived from cetuximab-covered cancer cells (49). The antitumor function can also be enhanced by NK-cell-DC cross-talk, which ensues after the recruitment of both NK cells and DCs to the inflamed areas caused by cancer, decreasing the activity and the number of immunosuppressive regulatory T cells.…”
Section: Discussionsupporting
confidence: 40%
“…Correale and colleagues found that a cytotoxic lymphocyte antitumor response was stimulated by dendritic cell (DC)-mediated cross-priming of antigens derived from cetuximab-covered cancer cells (49). The antitumor function can also be enhanced by NK-cell-DC cross-talk, which ensues after the recruitment of both NK cells and DCs to the inflamed areas caused by cancer, decreasing the activity and the number of immunosuppressive regulatory T cells.…”
Section: Discussionsupporting
confidence: 40%
“…Correale and colleagues demonstrated in vitro that cetuximab ameliorates DC-mediated phagocytosis of colon cancer cells, which thereby enhances CTL dependent anti-tumor response. 26 Our group has demonstrated substantial cross-presentation through enhanced NK:DC cross talk, 27 Cetuximab associated NK-cell induced DC maturation therefore influences TA cross-presentation. 13,27,28 This effect on adaptive immunity was also observed by Lou and colleagues, who reported effects on T cell diversity after a combination of cetuximab treatment with chemotherapy in a subgroup of patients.…”
Section: Discussionmentioning
confidence: 95%
“…138 Trastuzumab and cetuximab, monoclonal antibodies directed against tumor-associated receptor TK HER-2 and EGFR, respectively, augment antigen presentation through the formation of immune complexes, leading to stimulation of T-cell-mediated immune responses. 139,140 Altogether, these observations pave the way to clinical studies aimed at evaluating the possible synergism of targeted compounds and immunotherapy strategies.…”
Section: Box 1 Immune-based Effects Of Targeted Anticancer Compoundsmentioning
confidence: 95%